Assessment of Heavy Metal Pollution and Ecological Risk of Roadside Soils in Tlemcen (Algeria) Using Flame-Atomic Absorption Spectrometry. (13th October 2018) - Ramdani, Soumia; Amar, Amina; Belhsaien, Kamal; El Hajjaji, Souad; Ghalem, Said; Zouahri, Abdelmjid; Douaik, Ahmed
ABSTRACT: In Algeria, few studies have been conducted on the evaluation of roadside soil pollution. A total of 34 soil samples (28 roadside and 6 off-road) was obtained at 0–20 cm depth along the RN 35 national road. Heavy metal (Cd, Cr, Cu, Fe, Ni, Pb, and Zn) contents were extracted using aqua regia digestion and determined using atomic absorption spectrometry. Background values of heavy metal contents were determined using the robust statistical method of median plus two times the median absolute deviation. Single- and multi-element pollution and ecological risk indices were calculated. The results showed that background values were 2.5 ± 0.3, 64.9 ± 8.1, 28.0 ± 4.1, 29371.5 ± 4403.0, 32.9 ± 4.4, 72.2 ± 12.8, and 445.1 ± 62.9 mg/kg for Cd, Cr, Cu, Fe, Ni, Pb, and Zn, respectively. The results were all higher than their corresponding median values. Single-element pollution indices (enrichment factor and geoaccumulation index) showed that the pollution is primarily due to Pb and Zn. Multi-element pollution index (Nemerow index) indicated that only 3% of the soil samples are strongly contaminated, whereas 23% are seriously contaminated. The potential ecological risk index showed that Cd is the most harmful element, followed by Pb and Zn. 65% of the soil samples had moderate potential ecological risk, while only 3% had considerable potential ecological risk. This study may be used as a baseline for future monitoring and as a tool for decision-making regarding environmental protection policies and sustainability of this semiarid agroecosystem.